May Measurement Month 2019: an analysis of blood pressure screening results from Nigeria. (20th May 2021) - Wahab, Kolawole W; Kolo, Philip M; Odili, Augustine; Iwuozo, Emmanuel; Ifebunandu, Ngozi; Ademiluyi, Babatunde; Okunola, Oluyomi; Sani, Mahmoud U; Akinlade, Mathias; Isezuo, Simeon; Ale, Olagoke K; Beaney, Thomas; et al.
Abstract: The aim of this study is to estimate the frequency of undetected hypertension across the six geopolitical zones of Nigeria. We conducted an opportunistic screening of adults aged at least 18 years in the month of May 2019. Participants were recruited by trained volunteers using the May Measurement Month protocol. Blood pressure (BP) was measured using validated digital and mercury sphygmomanometers. We defined hypertension as BP ≥140/90 mmHg or the use of BP-lowering medication. A total of 3646 participants (52.8% females) with a mean age of 44.5 ± 15.7 years were screened. Hypertension was present in 39.2% of the participants but only 55. 4% of these were on antihypertensive medications. Only 46.8% hypertensives who were on medications had their BP controlled (<140/90 mmHg). Previous history of hypertension in pregnancy, alcohol intake and smoking were associated with increased mean systolic and diastolic BPs. The frequency of Nigerians with hypertension is high while only about half of those on antihypertensive medications are controlled. A multi-pronged approach to reduce the burden of hypertension is needed.